Con-patire: percezione e rappresentazione del dolore (Materiali di Estetica. Terza serie, 2024)
In this essay we intend to discuss the experience of pain starting from some phenomenological issues, and then examine three books that address the problem of how to consider the media representation of other people's pain. The theoretical proposal offered here consists in showing how the experience of pain is very complex and not at all reducible to something simple and immediate. The analyses of Stumpf, Brentano and Husserl demonstrate on the contrary how in experiencing even physical pain, issues related to corporeality, consciousness, affectivity and intra-subjective division come into play. Starting from these considerations, the question arises of how to understand the possibility of representing other people's pain through the use of image reproduction tools, in particular photography. Three authors, namely S. Sontag, L. Boltanski and G. Didi-Huberman, are discussed in order to bring out the complex dialectic implicit in every media representation of pain, which connects compassion and complacency. In all cases, what emerges is the awareness that the experience of pain is always an intersubjective structure and that the pain of others, far from being inexperienced, can on the contrary lend itself to multiple and divergent attestations.
Keywords: intersubjectivity; pain; phenomenology; photography; experience